The Influence of Islamic Banks and Sovereign Retail Sukuk on Economic Growth in Indonesia - Bella, Firsty Izzata; Inas, Inas (Faculty of Islamic Economics and Business Sultan Aji Muhammad Idris State Islamic University Samarinda, 2023)
This study aims to examine the short-term and long-term effects of Islamic banking financing and the development of sovereign Retail Sukuk (SR) on Indonesia's economic growth during the period 2009: Q1 to 2019: Q3. Outstanding SR is used as an indicator of SR’s development in seeing its impact on Indonesia's economic growth. Through Dickey Fuller-Generalized Least Square (DF-GLS) analysis, Lag-Length Test, Auto-Regressive Distributed Lag (ARDL), Cointegration Bound Testing. Total Sharia Bank financing and outstanding SR do not have long-term cointegration with Indonesia's economic growth. Meanwhile, in the short term, Indonesia's GDP is influenced positively by total Islamic Bank financing (TFIN) at lag 3 and negatively by the outstanding SR at lag 3 and 4. Researchers only examined the Islamic banking sector, specifically highlighting financing in Islamic banking and SR’s development through nominal outstanding on a quarterly scale. The limitations of the variables studied are becoming the limitations of this study. The government as a policymaker have to provide a support through cooperation between institutions and Medium and Small Enterprises (MSMEs) with Islamic banks in collecting and channeling financing, education, and outreach to the public. Consequently, the deepest layers need to be improved to make SR an individual investment instrument that can support Indonesia's economic growth. The implications of this study to offer valuable insights for policymakers, urging them to foster the growth of Islamic banks and promote retail Sukuk as an investment option and enhancing investors awareness of retail Sukuk.